2021
DOI: 10.3389/fphar.2021.683935
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles: A Hope for the Treatment of Inflammation in CNS

Abstract: Neuroinflammation, an inflammatory response within the central nervous system (CNS), is a main hallmark of common neurodegenerative diseases, including Alzheimer’s disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS), among others. The over-activated microglia release pro-inflammatory cytokines, which induces neuronal death and accelerates neurodegeneration. Therefore, inhibition of microglia over-activation and microglia-mediated neuroinflammation has been a promising strategy for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 221 publications
(236 reference statements)
0
32
0
Order By: Relevance
“…It has been reported that nanoparticles (NPs) that emerged with the developing technology could be useful tools for anti-inflammatory drugs throughout the BBB to inhibit the excessive activation of microglia and neuroinflammation. Therefore, NPs with proper biocompatibility have the potential to be developed as an effective carrier to help drugs cross the BBB or as a therapeutic agent for the treatment of neuroinflammation-mediated NDs [ 42 ]. According to the results of our study, it should be considered that the use of peripheral pathways in the struggle against inflammation may be insufficient in pwAD due to the peripheral inflammation being background compared to CSN inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that nanoparticles (NPs) that emerged with the developing technology could be useful tools for anti-inflammatory drugs throughout the BBB to inhibit the excessive activation of microglia and neuroinflammation. Therefore, NPs with proper biocompatibility have the potential to be developed as an effective carrier to help drugs cross the BBB or as a therapeutic agent for the treatment of neuroinflammation-mediated NDs [ 42 ]. According to the results of our study, it should be considered that the use of peripheral pathways in the struggle against inflammation may be insufficient in pwAD due to the peripheral inflammation being background compared to CSN inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological state of the brain is quite different to that of other organs because the BBB is a primary obstacle for drug delivery to the brain [25,26]. For this reason, various delivery platforms have been investigated to improve the penetration and/or transport of bioactive agents [26][27][28][29][30][31][32][33][34][35][36][41][42][43][44][45][46][47]. For example, surfactants such as polysorbate 80 have been used to allow nanoparticles or drug carriers to penetrate the BBB [41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Nano-dimensional carriers such as nanoparticles, liposomes, peptide-drugs and/or polymeric drugs have been investigated for the improvement of drug delivery across the BBB [27][28][29][30]. Nano-dimensional carriers are characterized by small particle sizes, diversity of customized form, ease of lipophilic drug encapsulation, increased half lives in the body, and targeting of the drug to specific sites of action [31].…”
Section: Introductionmentioning
confidence: 99%
“…26 Single-walled carbon nanotubes showed an antiinflammatory impact in a rat stroke model and prevented neurons from ischemia injury. 204 Local administration of SOD-loaded nanoparticles produced persistent protective implications resulting in a 65% decrease in infarct volume, whereas SOD solution therapy increased infarct volume by 25%. The prolonged lifespan of rats treated with nanoparticles indicated the superior protective impact of SODloaded nanoparticles.…”
Section: Stroke and Nanoformulations Of Synthetic Drugsmentioning
confidence: 99%